Web-Based Public Service Information System for the Economic and Development Sector - Allwine; Badiwibowo Atim, Sandi (Akademi Manajemen Informatika dan Komputer PARBINA NUSANTARA Pematangsiantar, 2025)
Tanah Merah is a sub-district located at Jl. G. Siinabung No.1, Tanah Merah, South Binjai District, Binjai City. This paper discusses a web-based information system for economic and development services (Ekobang) in Tanah Merah sub-district, Binjai City. From the research conducted, it is concluded that the current data processing system still utilizes Microsoft Word and Microsoft Excel, which, as we know, lack integrated databases, thus leading to potential data redundancy. To address this issue, a web-based Ekobang service information system was designed to facilitate residents in applying for IMB (Building Construction Permit) and SKU (Certificate of Business Domicile) recommendations quickly and easily. The developed system includes data input modules for IMB recommendations, SKU data, EKOBANG data, and user data. This service system was built using PHP and JavaScript programming languages with MySQL as the database. The testing results indicate that the system helps reduce the risk of data duplication.